Les installations portuaires romaines d’Incarville (Eure) - Laurent Paez-Rezende (Gallia)
The “Bas des Prés” settlement at Incarville (Eure) was discovered and partially excavated in 1995. Located halfway between Rouen/Rotomagus, capital of the territory inhabited by the Veliocasses, and Évreux/Mediolanum Aulercorum, capital of the territory of the Aulerci Eburovices, the ancient port facilities were established on the left bank of the major bed of the Eure river, near the Seine-Eure-Andelle confluence. The port facilities were comprised of a channel, a quay and a pier, occupying the wetland, and of several buildings erected on the terrace. The settlement, which could be reached by a road, included enclosed and peripheral areas. The channel is 1 km long, and is thought to originate 600 m upstream from the port. At its current section it is almost 25 m wide and in the center it is one metre deep. At the highest point of the site, on its left side, a large bank emerges in contact with the alluvial terrace. The quay and the pier were located on the bank of the channel. The 20-metres-long quay front, built along the axis of the channel, was made by a single alignment of sixteen blocks and three piles of limestone rubbles. The blocks were set on the first deposits of peat that silted up the bank. At the rear, compacted embankments constitute a vast platform extending from the blocks to the terrace. The pier was made of a wooden box and embankments connected to the edge of the terrace. It stretched over 17 m into the channel. Behind it, on both sides of the street, half-timbered buildings set on stone foundations were distributed over more than one hectare on the lower alluvial terrace. Three architectural complexes on stone foundations in particular testify to buildings that probably functioned mainly as warehouses. The fourth building exhibits a rectangular plan of 3.30 x 2.50 m evoking a small temple or an oratory. The site has yielded abundant waterlogged wooden pieces, mostly piles used for the construction of port equipment, as well as several elements which originated from dismembered boats and were subsequently reused. The chronological evolution of the port site spans more than five centuries. In this place a rural settlement existed previously (1st c. BC). The port structure dates to between the middle and the last quarter of the 1st c. AD (channel, bank and pier). The port activity reached its apogee between the end of the 1st c. AD and the end of the 3rd c. AD. This phase is marked by the dismantling of the southern half of the bank, in favour of the quay, while the pier was preserved. The last traces of port activities are attested to in the 4th and 5th c. AD, in particular through imports of ceramics in abnormally high proportions. Only the channel is still used. Occupation of the terrace continued until the 6th-7th c. AD, but without port activity. Located at the boundary between the territory of the Eburovices and that of the Veliocasses, the port of Incarville played the role of a staging post in the flow of goods circulating between the axis of the lower Seine valley and the hinterland. It can therefore be interpreted as a local economic player, a kind of trading post.